An Unfortunate Cause of Chronic Nausea and Vomiting: Mitochondrial Neurogastrointestinal Encephalomyopathy (MNGIE) - Neethi Dasu; Brian Blair; C. Jonathan Foster; Colin Smith (Case Reports in Gastrointestinal Medicine)
We present a unique case of a 24-year-old male who was admitted for intractable nausea, emesis, weight loss, and abdominal discomfort. The patient underwent an extensive workup and was diagnosed with mitochondrial neurogastrointestinal encephalopathy. Early diagnosis is critical to proper management of this disease process. MGNIE is a difficult disorder to diagnose given the complexity of the disease, and this case provides clinicians the proper understanding and management of such a unique and difficult diagnosis.